2011
DOI: 10.1007/s00266-011-9820-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Among Iranian Adults Before and After Rhinoplasty

Abstract: According to this study, QOL is improved after rhinoplasty in Iranian adult patients. With proper patient selection and a successful operation, improvement of physical and mental health can be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 24 publications
(31 reference statements)
0
27
2
Order By: Relevance
“…SF-36 is one of the most popular questionnaires which has been used to assess QOL. Ease of use, simple scoring system and interpretability of final scores are among the advantages of this questionnaire [13,14]. In the current study, QOL assessment results showed significant differences between patient and control groups apart from the SF-36 scores of pain (p<0.05), vitality (p<0.05), social functioning (p<0.05) and emotional role difficulties (p<0.05).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…SF-36 is one of the most popular questionnaires which has been used to assess QOL. Ease of use, simple scoring system and interpretability of final scores are among the advantages of this questionnaire [13,14]. In the current study, QOL assessment results showed significant differences between patient and control groups apart from the SF-36 scores of pain (p<0.05), vitality (p<0.05), social functioning (p<0.05) and emotional role difficulties (p<0.05).…”
Section: Discussionmentioning
confidence: 55%
“…The final scale has totally 14 items, with responses being scored on a scale of 0-3, with 3 indicating highersymptom frequencies. Score for each subscale (anxiety and depression) can range from 0-21 with scores categorized as follows: normal (0-7), mild (8-10), moderate (11)(12)(13)(14), severe (15)(16)(17)(18)(19)(20)(21). Scores for the entire scale (emotional distress) range from 0-42, with higher scores indicatingmore distress.…”
Section: Methodsmentioning
confidence: 99%
“…GHQ-28 has four subscales that assess somatic symptoms (items 1-7), anxiety (items [8][9][10][11][12][13][14], social withdrawal (items [15][16][17][18][19][20][21], and depression (items [22][23][24][25][26][27][28]. 20 Each item has four optional responses scoring between 0 and 3 as score 0 is for "not at all," score 1 for "no more than usual," score 2 for "rather more than usual," and score 3 for option "much more than usual."…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11] QOL changes after cosmetic surgeries has been evaluated in various studies that according to the type of surgery different results have been obtained. [12][13][14][15][16] Some studies have shown improvement in QOL and self-esteem after plastic surgery, 16,17 but some other studies did not show beneficial effects of cosmetic surgery on patients QOL and mental health. 18 As in most cases, esthetic surgeries are performed to improve individuals' satisfaction with their appearance and also to improve their psychological health by improving self confidence and self-esteem, 11,19 we sought to know whether such improvement really is obtained following cosmetic rhinoplasty or not.…”
Section: Introductionmentioning
confidence: 98%
“…They study showed that patients' QoL was enhanced after rhinoplasty [15]. Fatemi MJ et al, in 2012, using the same questionnaire examined the QoL of Iranian patients undergoing rhinoplasty. Similar to the findings of the present study, Fatemi MJ et al, showed that rhinoplasty improved the patients' QoL in all domains, including physical functioning, role of emotion, bodily pain, and vitality [10].…”
Section: Discussionmentioning
confidence: 99%